Kajian Drug Related Problems Pasien Otitis Media Supuratif Kronis di Bangsal THT RSUP. Dr. M. Djamil Padang - Suhatri Suhatri; Popy Handayani; Harisman Harisman (Jurnal Sains Farmasi & Klinis, 2017)
A study of drug related problems in patients with chronic suppurative otitis media has been done in the ENT ward of Dr. M. Djamil Hospital Padang. The study was conducted retrospectively and prospectively by tracking the patient’s condition, medical record, Drug Instruction Card (KIO) and nursing care records in patients with chronic suppurative otitis media. The data obtained is then analyzed descriptively. The results showed that the most prevalent DRPs category was drug interactions. There were 10 cases of drug interactions of 11 DRPs incidents from retrospective data and 5 cases of drug interaction of 10 DRPs incidents from prospective data in chronic suppurative otitis media in the ENT ward of Dr. M. Djamil Hospital Padang. The other DRPs categories were from dose retrospective data of less than 1 case (3.84%) and from prospective data of adverse drug reactions of 5 cases (45.45%). From the results of this study, it can be concluded that the category of drug related problems found in patients suppurative chronic otitis media in the ENT ward of Dr. M. Djamil Hospital Padang is drug interaction, less dosage, and adverse drug reactions.